Malaysian commercial law - Muhammad Rizal bin Razman; Syahirah Binti Abdul Shukor
This book provides information and guidance on Malaysian Commercial Law where has been divided into six relevant topic. The topics are Law of Contract, Law of Hire-Purchase, Law of Agency, Law of Sale of Goods, Lawa of Insurance and Law of Negotiable Instruments.